Cinematherapy in Islamic Counseling: A Novel Approach to Supporting Children’s Psychological and Religious Growth - Mz, Ihsan; Marhani, Isnaeni; Sun, Xiaohui; Halima, Andi (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
counseling as an innovative approach to foster the psychological and religious growth of children in conflict with the law (andikpas) at Lembaga Pembinaan Khusus Anak (LPKA) Kelas II Kota Palangka Raya, Indonesia. While conventional cinematherapy is widely recognized, its application within an Islamic framework remains underdeveloped. Using a qualitative explanatory design, this research employed structured interviews and thematic analysis to explore the therapeutic process and its impacts. The findings introduce the Islamic-Integrated Cinematherapy Protocol (IICP), a structured model consisting of perceptual, reflective, and transformative pillars. This protocol utilizes film as a catalyst for mukasyafah (spiritual self-disclosure), bypassing cognitive barriers to stimulate the qalb (heart) toward deep muhasabah (introspection). The results indicate that this approach effectively enhances emotional regulation and self-awareness while internalizing core Islamic virtues, specifically Sabr (patience), Tawakkal (spiritual reliance), and Taubat (repentance). By bridging visual-cognitive stimulation with faith-based reflections, this study fills a critical gap in culturally sensitive therapeutic literature, offering a "spiritual decolonization" model that is ready for practical adoption by practitioners in correctional and educational settings.